Trends and Disparities in the Prevalence of Childhood Obesity in South Texas between 2009 and 2015 - Byron A. Foster; Trevor M. Maness; Christian A. Aquino (Hindawi Limited, 2017)
Background. Recent reports have highlighted possible decreases over time in obesity, particularly among children aged 2-5 years. Hispanic children experience significantly higher obesity rates, and less is known about trends for Hispanic children. Methods. A large healthcare system-based dataset from south Texas was used to analyze body mass index (BMI) values obtained clinically from 2009 through 2015. Age and race/ethnicity specific prevalence of overweight and obesity were calculated using CDC standards and trends were examined over time using regression analyses, and mapping software was used to identify geographic variation. Results. Hispanic children in south Texas experience levels of obesity (25.3%, 95% CI: 25.1-25.6) significantly higher than their white (16.6%, 95% CI: 16.0-17.2) or black (18.2%, 95% CI: 17.3-19.1) peers. Obesity in Hispanic children aged 2-5 years decreased from 18.5%, 95% CI: 16.6-20.5, in 2009 to 15.1%, 95% CI: 14.3-15.9, in 2015. Obesity in Hispanic adolescents was stable at 30.4%, 95% CI: 28.5-32.4, in 2009 and 31.3, 95% CI: 30.3-32.2, in 2015. Conclusions. While obesity decreased in the youngest age group of Hispanic children, south Texas continues to experience high levels of obesity that exceed national averages with significant disparities.